Flaring radio lanterns along the ridge line: long-term oscillatory motion in the jet of S5 1803+784 - Kun, Emma; Karouzos, Marios; Gabányi, Krisztina Éva; Britzen, Silke; Kurtanidze, Omar M.; Gergely, L. Á (Monthly notices of the Royal Astronomical Society, 2018)
ABSTRACT. We present a detailed analysis of 30 very long baseline interferometric (VLBI) observations of the BL Lac object S5 1803+784 (z= 0.679), obtained bet